Analysis of traffic accidents using association rules mining technique / Abdullah Murshid Abdul Rahim - Abdul Rahim, Abdullah Murshid (2022)
Through the use of technology, particularly business analytics and data mining, people, businesses, and business owners are able to make better decisions and manage their operations more easily. Analysis of traffic accidents using data mining techniques is a project to identify the traffic accident pattern analysis using data mining techniques. A dataset from Kaggle is used. The primary focus of this project is the patterns of traffic accidents in Addis Ababa. The issue the Addis Ababa Sub City Police Departments are facing is that over the years, the road traffic accidents were manually recorded, making it challenging to pinpoint the issues and develop solutions. As a result, this study was created to discover the trends in road traffic accidents using the prediction technique. The CRISPDM methodology was used to conduct this study. The modelling technique used in this research association rules mining. WEKA software was used to perform modelling. To help the user quickly understand the findings from this research, the findings from the modelling technique used have been visualized in the dashboard created using Tableau. In conclusion, the positive results of the association rules mining will undoubtedly effectively reduce traffic accidents and aid the Addis Ababa Sub city police departments in making decisions.